The association between ondansetron use and mortality risk of traumatic brain injury patients: a population-based study - Wang, Ruoran; Zhang, Jing; Xu, Jianguo; He, Min (Frontiers in Pharmacology, 2024)
Background: Traumatic brain injury (TBI) patients suffer high risks of mortality. Ondansetron has been verified effective in improving the prognosis of some kinds of critically ill patients. We design this study to explore whether the ondansetron use is associated with lower risks of mortality among TBI patients. Methods: TBI patients from the Medical Information Mart for Intensive Care-III were collected. The usage of ondansetron including intravenous injection and oral tablet since admissions to the Beth Israel Deaconess Medical Center between 2001 and 2012 was identified. Univariate and multivariate logistic regression were performed to analyze the relationship between the ondansetron use and mortality of TBI. Propensity score match (PSM) was utilized to generate balanced cohorts of non-ondansetron use group and ondansetron use group. Sub-group analysis was performed to verify the association between the ondansetron use and mortality of TBI in different TBI severity after PSM. Results: In TBI cohorts before PSM, the usage incidence of ondansetron was 37.2%. The 30-day mortality was significantly lower in the ondansetron group (p<0.001). The multivariate logistic regression showed ondansetron were associated with the lower mortality of TBI (p=0.008). In TBI cohorts after PSM, the 30-day mortality of the ondansetron group was lower than the non-ondansetron group though without statistical significance (p=0.079). Logistic regression indicated ondansetron use was significantly associated with the lower mortality of moderate to severe TBI (p<0.001) but not mild TBI (p=0.051). And Cox regression also presented ondansetron use was significantly associated with the lower mortality of moderate to severe TBI (p<0.001) but not mild TBI (p=0.052). Conclusion: Ondansetron usage is associated with a lower mortality risk of moderate to severe TBI but not mild TBI patients. The ondansetron may be a novel adjunctive therapeutic strategy to improve the prognosis of moderate to severe TBI patients.